Impact of prophylactic oral azithromycin during labor on Azithromycin Resistance (AMR) in nasal Staphylococcus aureus and Streptococcus pneumoniae in women and infants in the multi-country Azithromycin Prevention in Labor Use Study (A-PLUS) - Patricia L. Hibberd; Jean H. Kim; Marissa Trotta; Sixto M. Leal; Anna Aceituno; Doyle V. Ward; Archana Patel; Akila Subramaniam; Waldemar A. Carlo; Imran Ahmed; Sarah Saleem; Sk Masum Billah; et al. (PLoS ONE, 2026)
Background Prophylactic oral azithromycin vs. placebo reduced maternal, but not neonatal, mortality/sepsis in the A-PLUS Randomized Trial. While prophylactic intrapartum azithromycin reduces maternal mortality/sepsis, it may promote antimicrobial resistance (AMR) in commensal bacteria,. Methods Randomly selected women and their infants participating in A-PLUS were enrolled in a longitudinal cross-sectional sub-study to assess the presence of azithromycin resistance in selected bacteria in nasal cultures. Staphylococcus aureus and Streptococcus pneumoniae were cultured on selective agar, then azithromycin-containing agar to select for azithromycin resistant bacteria, identified biochemically. Azithromycin susceptibility was assessed by E-test. Nasal cultures were collected from women and infants between August 11, 2021 and September 18, 2023 during labor/day 1, day 7, 6 weeks, and 3, 6 and 12 months after delivery. Results The study enrolled 911 women and 915 liveborn infants at 8 sites in 7 countries. Azithromycin resistance in S aureus was higher and azithromycin susceptibility was lower in women receiving azithromycin compared with those receiving placebo on day 7 (P < 0.001), 6 weeks (P < 0.001) and 3 months (P = 0.009) after delivery. Azithromycin resistance in S aureus was also higher and azithromycin susceptibility was lower 6 weeks after delivery (P < 0.001) in infants born to women receiving azithromycin, Azithromycin resistance in S. pneumoniae was too sparse to interpret. Conclusions There was an increase in prevalence of azithromycin resistance (or reduction in azithromycin susceptibility) in commensal nasal S. aureus between day 7, 6 weeks and 3 months in women exposed to azithromycin vs. placebo and only at 6 weeks in infants exposed to azithromycin vs. placebo. These differences between the azithromycin and placebo groups were no longer detected at 6 and 12 months post-partum in the women and after 6 weeks through 12 months in the infants.